Analisis Peran Kurikulum dan Standar Penilaian Dalam Pendidikan di Indonesia - Endang, Heri Kus (Yayasan Darusssalam Bengkulu, 2021)
Curriculum plays a very important role in the world of education as a guide to future educational goals so that it runs better and optimally. In implementing the curriculum, it is developed in schools to adapt to environmental conditions and needs, because these things are related to each other within it and become a reference for all parties who play a role in implementing the applicable curriculum. The curriculum process includes planning, organizing, implementing, monitoring and evaluating. Building a good curriculum certainly requires in-depth study and thought. Evaluation as the final process of a curriculum is used as a benchmark for curriculum achievement. Education is basically a human effort to improve knowledge, both obtained from formal and informal institutions. To achieve this, appropriate educational goals are needed. The goals of education will determine success in the process of forming the human person, of course balanced with other elements in education. The purpose of writing this article is to analyze the important role of the curriculum in achieving educational goals.